Strategic Landscape Planning Using THEMEQUAL for Sustainable Theme Park Project Success: Case BSD City Theme Park - Ganesya, Ageng Ramadana; Rimawan, Erry; Amin, Mawardi (Program Pascasarjana Magister Teknik Industri Universitas Mercu Buana, 2025)
The long-term success of theme parks is highly dependent on the integration of robust structural quality and exceptional service delivery. This study examines the influence of strategic landscape planning—using the THEMEQUAL framework—on project outcomes, focusing on BSD City Theme Park, Indonesia. Utilizing Structural Equation Modeling-Partial Least Squares (SEM-PLS) on responses from 400 theme park visitors, findings show that both structural quality (β = 0.36, p < 0.001) and service quality (β = 0.41, p < 0.001) have strong, significant effects on visitor satisfaction. Visitor satisfaction, in turn, is a significant predictor of project success (β = 0.47, p < 0.001), mediating the effects of both structural and service quality. Indirect (mediation) effects account for 62% of the total influence on project success. These results demonstrate that improved construction robustness and service standards significantly elevate satisfaction (mean index = 4.18/5), visitor loyalty, and positive word-of-mouth, underpinning sustainable project viability. Practical implications highlight that integrating strategic landscape planning and superior service quality is essential for achieving sustained competitive advantage in Indonesia’s growing theme park sector.